(3eQKjI CHh GdMSf GdJgGei jQKi HgG hdOgs - (3Ydj Hf eMeO Hf agO, CHh GdMSf GdJgGej,J (B416 (3g` s ((3YeQ CfSi Hf eMeO OjH GdUbYGf s)
(3ChdgG (B:s
(3Mce GdefjI ai GdHQjI LGQi eG gPg GdOfjG HZjQ bQGQ s
(3BNQgG (B:s
(3hdQHeG EYJUe GdYdje HLGgd dGNjQ ai jefi HZjQ jSGQ s
(3HgG fXGe GdJYbjHIs
(3YOO CHjGJ GdbUjOI (B83 (3HjJs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B145 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B219s
Keywords: (3GdCOHs